Analysis of Amylase Activity in Bacteria Isolated from Hot Spring of Pentadio Resort - Nur'ain Marton Angio; Aryati Abdul; Syam S. Kumaji; Wirnangsi Din Uno; Yuliana Retnowati; Magfirahtul Jannah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS (JPBN), 2024)
The hot spring of Pentadio Resort is one of the geothermal areas likely to be the place of bacteria or microorganisms that can produce amylolytic enzymes. This research aims to analyze bacteria in the Pentadio Resort hot springs that possess the potential to produce amylase enzymes, analyze the characteristics of bacterial isolates that produce amylase enzymes in Pentadio Resort hot springs and determine the types of bacteria that produce amylase enzymes in Pentadio Resort hot springs. The research employs a qualitative and descriptive method. The research involved several methods, including sample collection, media preparation, isolation and selection of thermophilic bacterial isolates, purification of thermophilic bacterial isolates, selection of isolates producing amylase enzymes, identification of selected isolates (motility test, biochemical test, gram staining), and molecular identification. The research yielded seven isolates, and isolate code A6 demonstrated the potential to produce amylase enzymes with a clear zone size of 23,26 mm, bacillus, gram positive, and positive motility. Subsequently, molecular identifidation was carried out in which, based on the results of phylogenetic tree reconstractiopisalate A6 was related to the bacteria Bacillus cereus strain MD 152, which belongs to the Bacillus cereus bacteria